Effect of Sugarcane Bagasse on Growth Performance of Hereropneustes fossilis (Bloch.) Fingerlings - E. Sugumaran, M.V. Radhakrishnan* and (Journal of Experimental Sciences, 2010)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; background: white; padding-bottom: 0in; border-left: medium none; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The present investigation has been conducted to evaluate the effect of sugarcane bagasse as an artificial substrate on growth performance of Heteropneustes fossilis figerlings for a period of 120 days. Sugarcane bagasse bundles (Length 50 cm; diameter 4cm) of 5 kg were hung in large cement tanks (5x5x1 m) with 15 cm soil base with well water in 6 of the 9 tanks randomly at the rate of 5 kg each, by suspending the bundles at regular distances from bamboo poles kept across the tanks. Fingerlings of H. fossilis (av. wt. 3.15 g) were stocked at 40 per tank two weeks after the addition of manure and substrate. No feed was provided to the fish in 3 of the substrate-added tanks (T1), while a pelleted diet was fed to the fish in the remaining 3 substrate-added tanks (T2) and the other 3 tanks without substrate (T3). Individual fish in each tank were weighed at the start and every 14 days to monitor growth response and feed utilization. Water quality parameters (dissolved oxygen, pH and ammonia) were also monitored. Fish growth performance and nutrient utilization were determined for fish Mean weight gain (MWG), Specific growth rate (SGR), Protein efficiency ratio (PER), Feed conversion Ratio (FCR), Protein intake (PI) and fish Survival rates (SR %). Fish carcass was also analyzed for crude protein, lipid and ash in all treatments at the end of 120 days. The weight gain of the fish showed a significant response. Specific growth rate showed a high value in bagasse and supplemental feed group (T2) followed by sugarcane bagasse alone used group (T1). The feed intake value is more or less similar in all the three groups. PER and FCR values also showed high in substrate + supplemental feed group. The survival rate value recorded maximum in T1 group. In fish carcass composition, the dry matter showed the order T2>T3>T1. Crude protein and lipid values are more in substrate alone added group (T2), but the ash value is more in T1 group. These results showed that sugarcane bagasse can effectively be use as a substrate for the culture of the catfish Heteropneustes fossilis.